The Transferability of Socialand Cultural Anthropology into the Diverse Field of Education in Differing EU Countries - Markom, Christa (Łódzkie Studia Etnograficzne, 2020)
This paper discusses the EU project TRANSCA – Translating Socio-Cultural Anthropology into Education. The project shares current practices and ideas to help anthropology become more widespread in teacher education and subsequently, in schools. The paper questions selected concepts (e.g. Funds of Knowledge) and the intentions of translating anthropological knowledge for educational purposes because of the problematic notion of „translation” itself in anthropology.